The importance of the elements of game stoppage for the final score of a football match - Radoman, M.; Smajic, M. (Serbian Journal of Sports Sciences, 2008)
The research was done on the sample of 64 football matches played at FIFA World Cup Germany 2006 and 128 scores were divided according to three possible scores: victory, defeat, and draw. The main aim of the study was to establish the importance of interrupting a football match for the final score (victory, defeat or draw). According to the results and their interpretation it can be concluded that the results of the data analysis show that there were significant differences concerning the frequency of final scores relative to the analyzed elements of game stoppage. Even though the differences observed were not equally distributed in all classifications, the results show that there were significant differences concerning the analyzed elements of a football match. The analyses justified the hypothesis that important statistical differences exist with all analyzed elements of game stoppage concerning particular final scores of football matches (victory, defeat or draw). The difference in the elements of game stoppage was a consequence of different choice of tactics and techniques as well as the possibility of their realization during attack and defense.